Evaluation of imidazolium-based ionic liquids for biogas upgrading. (1st August 2016) - Xie, Yujiao; Ma, Chunyan; Lu, Xiaohua; Ji, Xiaoyan
Highlights: The database of three ILs was implemented in Aspen plus. The process simulation of biogas upgrading using ILs was performed. The effects of property of ILs and operational parameters were investigated. The ILs scrubbing was compared with water scrubbing and aqueous ChCl/Urea scrubbing. Abstract: The conceptual processes for biogas upgrading using three imidazolium-based ionic liquids ([hmim][Tf2 N], [bmim][Tf2 N] and [bmim][PF6 ]) were simulated in Aspen Plus to study the effect of properties of ionic liquids (ILs) on the process performance. To conduct the process simulation, each IL was input into Aspen Plus as a pseudo component, their critical properties were estimated by group contribution method, and their thermo-physical properties were correlated from the available experimental data by semi-empirical equations. The gas solubility in ILs was modeled with the non-random two-liquid model and Redlich–Kwong equation of state. Among the studied ILs, the simulation results show that the amount of recirculated solvents and the total energy consumption for upgrading process using ILs follow: [bmim][Tf2 N] < [bmim][PF6 ] < [hmim][Tf2 N]. The effects of density and viscosity of ILs on pressure drop and diameter of the absorber as well as the effects of operational pressures and temperatures on the process efficiency were investigated. It is found that the energy consumption increases with increasing pressure and temperature in the absorber and decreases with increasing pressure in the first flash tank. The ILs-based technology was further compared with water scrubbing and aqueous choline chloride/urea scrubbing, and the comparison shows that the total energy consumptions follow: 50%ChCl/Urea-water < [bmim][Tf2 N] scrubbing < water scrubbing.